The Analysis of Figurative Language Used in Chapter 1-30 of Psalm in King James Version Bible - Charissa Bonita Yenita Resi; Adrallisman Adrallisman (e-LinguaTera, 2021)
This study entitled An Analysis of Figurative Language Used in Chapter 1-30 of Psalm in King James Version Bible. The purpose of the study is to find out the kind of figurative language which is used by The Book of Psalm in King James Version Bible and also to find out the meaning of the figurative language which is applied in The Book of Psalm in King James Version Bible. The writer used theory Figurative Language from X.J Kennedy, Knickerbocker & Renninger, Keraf, Wren & Martin, Pradopo, Fatimah, and Gunter Radden. The method applied in this research is descriptive qualitative method. These are 5 kinds of figurative languages which are analyzed Simile, Idiom, Metaphor, Hyperbole and Paradox. Every data has been reviewed and the writer take conclusion that most of figurative language that is used in this book is Metaphor. There are 12 cases of metaphor that can be found. Then Simile with 7 cases, Idiom with 7 cases, Hyperbole with 3 cases, and last is Paradox with 2 cases from 30 chapters the book of psalm. The most frequently word used is metaphor because there are so many words that have the similarities between the two things. This research highly expected to give information and knowledge to the reader or the next researcher to be able know about types figurative languages, meaning of figurative language, and to identify figurative language easier.